In Vitro Measurement of the Elastic Properties of the Native Red Blood Cell Membrane - V. A. Sergunova; E. K. Kozlova; E. A. Myagkova; A. M. Chernysh (Общая реаниматология, 2015)
Objective: to develop a procedure to image native cells in a physiological medium and to measure the local stiffness of fixed red blood cell membranes in liquid in vitro experiments.Material and methods. Blood was taken from 4 healthy donors during prophylactic examinations and placed in EDTA-containing Microvette tubes. The red blood cells were fixed in buffer solution onto a polylysine-coated substrate. Cell images were obtained using an ACM NTEGRA Prima microscope (NT-MDT, the Russian Federation). Membrane stiffness was estimated by atomic force spectroscopy.Results. The values of effective Young's modulus were obtained for a statistical sample of fixed red blood cell membranes. Under the action of verapamil on blood, Young's modulus was equal to 528±21 kP. Under the action of heavy metal ions on blood, the mean local stiffness of the dried membrane was increased up to 942±56 at a depth of 35 nm.Conclusion. The measurements of the force characteristics of red blood cells in liquid can yield reproducible results of examining the elastic properties of the membranes. Atomic force microscopy and atomic force spectroscopy can be employed analyze the properties of a live cell in the physiological medium.